Przygraniczna współpraca państw członkowskich UE w zakresie świadczenia usług zdrowotnych - Bazylińska-Nagler, Justyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Since Lisbon Treaty came into force the EU has been empowered to initiate cooperation between Member States in order to improve medical services complementarity in MS’ border regions (Article 168 (2) TFUE). Through this new legal basis the UE may have impact on the MS’ independent actions within this area. Moreover, new Patient Mobility Directive regulates this kind of cooperation too. Undoubtedly, cooperation concerning medical services delivery in border regions may be fruitful both for service providers and patients, at the same time it generates practical problems that could only partially be solved through this directive implementation. This article is aimed at patient mobility in border regions appraisal and leads to the final conclusion that improvement of the quality and quantity of cross-border cooperation in border regions still depends on the political will of Member States rather than the EU powers and initiatives.
Keywords: patients’ rights; Patient Mobility Directive; freedom to provide services; border regions; healthcare; cross-border cooperation